Four new species of Australian velvet ants (Hymenoptera: Mutillidae, Aglaotilla) reared from bee and wasp nests, with a review of Australian mutillid host records - Taylor, Christopher K.; Murphy, Mark V.; Hitchen, Yvette; Brothers, Denis J. (Zootaxa, 2019)
Four species of velvet ants (Mutillidae) were reared from nests of solitary bees and wasps collected using trap nests in southwest Australia and identified using morphological and DNA barcoding approaches. All four species, Aglaotilla micra sp. nov., A. lathronymphos sp. nov., A. chalcea sp. nov. and A. schadophaga sp. nov., are described as new, the last three from both sexes. A. micra, A. lathronymphos and A. chalcea are parasitoids of wasps in the genera Pison and Aulacophilinus (Crabronidae), with A. chalcea also recorded from Paralastor (Vespidae). Aglaotilla schadophaga is a parasitoid of bees in the genus Megachile (Megachilidae). The biologies and known hosts of Australian Mutillidae are reviewed. Photographs are also provided of type material for Ephutomorpha aeneidorsis Turner, 1914 (=Aglaotilla discolor Brothers, 2018), Mutilla metallica Smith, 1855 and Ephutomorpha subelegans Rayment, 1933. The lectotype of E. subelegans is formally designated.